Effect of Gender Based Violence on Women’s Health and Wellbeing in Northern Division Kabale Municipality. - Ninsiima, Irene (Kabale University, 2024)
The study was about the effects of Gender Based Violence on Women’s Health and Wellbeing in the Northern Division, Kabale Municipality. The study was guided by three objectives which were: (i) to find out the forms of Gender Violence in Northern Division, Kabale Municipality, (ii) to determine the impact of Gender Violence on the well-being of people in Northern Division, Kabale Municipality, (iii) to suggest the possible measures of curbing down Gender-Based Violence in Northern Division, Kabale Municipality. A targeted population of 60 respondents was considered for the study. These included the principal town Clerk of the Northern Division, CDO, Staff, and community members. Both simple random and purposive sampling techniques were used in identifying the study sample size. The methods that were used in data collection included questionnaires, observation, and interviews. Data collected was edited, coded, entered into a computer, and analyzed with Excel, a Microsoft statistical package, the results were presented in tables. Based on the results from the study, 100% of the respondents agreed that there are various forms of Gender-Based Violence in the Northern Division, Kabale Municipality. These included Physical Abuse, Sexual Abuse, Psychological Abuse, Emotional Abuse, Economic Abuse. The study findings revealed the impact of Gender Violence on the wellbeing of people in Northern Division, Kabale Municipality and these included the low economic status and poverty of women within and outside of marriage, women in abusive relationships frequently change or lose their employment. Gender Violence has also resulted in women losing time needed for productive work, Gender Violence also has an impact on girls' education, and Gender Violence often sabotages women’s efforts to gain employment, and acquire job skills. From objective three, it was found out as indicated by the respondents from Northern Division, Kabale Municipality that there are possible measures for curbing Gender Based violence in Northern Division, Kabale Municipality. These included understanding the specific root causes of GBV in each country and community, believe and supporting survivors, engaging men as allies and partners, challenging other gender norms, pay special attention to high-risk groups. The researcher concluded that there are some forms of Gender-Based Violence in the Northern Division, Kabale Municipality. These included Physical Abuse, Sexual Abuse, Psychological Abuse, Emotional Abuse, Economic Abuse.